2023
DOI: 10.3390/ijms24043849
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Prkcaa Links Social Behavior Defects with Disturbed Circadian Rhythm in Zebrafish

Abstract: Protein kinase Cα (PKCα/PRKCA) is a crucial regulator of circadian rhythm and is associated with human mental illnesses such as autism spectrum disorders and schizophrenia. However, the roles of PRKCA in modulating animal social behavior and the underlying mechanisms remain to be explored. Here we report the generation and characterization of prkcaa-deficient zebrafish (Danio rerio). The results of behavioral tests indicate that a deficiency in Prkcaa led to anxiety-like behavior and impaired social preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…Hu et al [ 3 ] studied the importance of PRKCA in regulating social interactions and social behavior by analyzing a PRKCA-deficient zebrafish model (Danio rerio). The molecular analysis conducted showed that Prkcaa and Prkcab were actively expressed in several tissues, except liver.…”
mentioning
confidence: 99%
“…Hu et al [ 3 ] studied the importance of PRKCA in regulating social interactions and social behavior by analyzing a PRKCA-deficient zebrafish model (Danio rerio). The molecular analysis conducted showed that Prkcaa and Prkcab were actively expressed in several tissues, except liver.…”
mentioning
confidence: 99%